Transmission Of Disaster Information In Implementing Relocation Policies After The Earthquake, Tsunami And Liquefaction In Palu, Central Of Sulawesi: Transmisi Informasi Kebencanaan Dalam Penerapan Kebijakan Relokasi Pasca Gempa Bumi, Tsunami Dan Likuifaksi Di Palu Sulawesi Tengah - Syamsul Bahri (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2024)
This study examines the transmission of information in the implementation of post-earthquake, tsunami, and liquefaction relocation policies in Palu, Central Sulawesi. The background of this study is the existence of problems in the relocation process characterized by miscommunication between the government and affected communities, as well as between the central, provincial, and city governments. The study aims to evaluate the impact of information transmission on the effectiveness of relocation policy implementation. The method used is a qualitative approach with document analysis and field observation. The results of the study indicate that ineffective communication causes information distortion and confusion among the community and policy implementers. In addition, weak bureaucratic support and differences in policy interpretation between levels of government worsen the situation on the ground. This study concludes that to improve the effectiveness of relocation policies, better communication and stronger collaboration between stakeholders are needed, so that policies can be implemented consistently and on target